Specific Inhibition of Endotoxin Coating of Red Cells by a Human Erythrocyte Membrane Component - Springer, Georg F. (1970)
We have isolated from human erythrocyte ghosts a fraction which prevents the attachment of unheated as well as heated lipopolysaccharides of gram-negative bacteria to red cells. This material has no significant inhibitory effect either toward the Vi antigen of gram-negative bacteria or towards the group and common antigens of the gram-positive bacteria investigated. We, therefore, named this fraction “lipopolysaccharide receptor.” The receptor interacts with lipopolysaccharides and not with erythrocytes, it forms complexes with and blocks those groupings of lipopolysaccharides which attach to red cells. The effect of the receptor is physical and not enzymatic. The interaction of the receptor with the lipopolysaccharides is reversible, and the receptor removes lipopolysaccharides fixed to red cells. An equilibrium of lipopolysaccharide distribution between cells and receptor is established when receptor-lipopolysaccharide complexes are incubated with red cells. The receptor is labile toward heat and deviation of the hydrogen ion concentration from neutrality; aldehydes destroy its inhibitory activity.